Analisis patahan veneer indirek resin komposit yang direkatkan pada email menggunakan dua resin semen berbeda - Octarina Octarina; Yosi Kusuma Eriwati; Andi Soufyan (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2012)
Indirect resin composite veneer restoration (VIRK) is used as esthetic restoration for anterior teeth. Attachment between restoration and enamel surface was obtained using multi-step (MS) resin cement. Recently, a one step self-adhesive dual-cured resin cement (SADRC) was introduced. Determine failure analysis of VIRK bonded to enamel using MS resin cement and SADRC. Twenty specimens of buccal surface of enamel premolar were used. The specimens were flattened using silicon carbide no.2000. VIRK cylindrical specimens (diameter 3mm, thickness 3mm), were light-cured in Solidilite chamber (Shofu, Japan) for 3 minutes. VIRK specimens were then divided into: Group I with Multi-step resin cement (n=10) and Group II with SADRC (n=10). After 24h in incubator (37oC), Shear Bond Strength (SBS) were tested using Universal Testing Machine(Shimadzu AG5000). Failure analysis was determine using Stereomicroscope (Nikon, Japan) and Scanning Electron Microscope ( JEOL JSM 6510LA, Japan). Data were analyzed using Independent Sample T-Test (p<0.05). The average SBS value of group VIRK+MS was (16.97 + 7.67 MPa) higher than VIRK+SADRC (7.17 + 3.67 MPa). VIRK+Multi-step group has mixed failure, while VIRK+SADRC group has adhesive failure. Mixed failure shows strong bond between VIRK and enamel using Multi-step resin cement.